Effect of cerium on yttrium-doped barium zirconate with a ZnO sintering aid: Grain and grain boundary protonic conduction. Issue 23 (1st December 2021) - Kim, Hye-Won; Seo, Jun; Yu, Ji Haeng; Yun, Kyong Sik; Joo, Jong Hoon; Moon, Jooho; Park, Hee Jung
Abstract: The grain and grain boundary protonic transport of yttrium-doped barium zirconate has been investigated for various Ce-substituted concentrations, and the origins of blocking on the grain and grain boundary resistances are considered. Ba(Zr1-x Cex )0.85 Y0.15 O3-δ samples (BZCY, x = 0, 0.05, 0.1, and 0.2) with a ZnO sintering aid have been prepared via conventional ceramic processing, and their grain and grain boundary resistances have been experimentally measured as a function of temperature under humid conditions using 2-probe AC impedance measurements. In the grain, a high-Ce-substituted sample with a large lattice volume is more conductive than a low-substituted specimen. The high-Ce-substituted sample also exhibits low resistance to the grain boundary. In the investigation of the origin of current blocking on the grain boundary, it is found that the space charge significantly affects grain boundary transport in the low-Ce-substituted sample. However, other mechanisms such as the charge-neutral effect (structural effect) of the grain boundary transport in the high-Ce-substituted samples are considered. In terms of the total conductivity (the summation of the grain and grain boundary components) of BZCY, it is found that the highest Ce-substituted barium zirconate (x = 0.2) exhibited the highest conductivity, demonstrating that it can potentially be utilized as a solid electrolyte in electrochemical devices such as solid oxide fuel cells.